2001
DOI: 10.1001/archneur.58.5.806
|View full text |Cite
|
Sign up to set email alerts
|

Acute Severe Spinal Cord Dysfunction in Bacterial Meningitis in Adults

Abstract: We demonstrate for the first time the MRI findings of adults with acute spinal cord involvement during bacterial meningitis. Magnetic resonance imaging showed central intramedullary hyperintensities on T2-weighted images that extended from the cervical to the lumbar cord, indicating myelitis. Clinical follow-up examinations suggest that myelitis during bacterial meningitis has an unfavorable prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 16 publications
1
54
0
3
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15] Table 2 summarizes findings from previous case reports. Of note is the fact that S.aureus myelitis has been described even without contiguous spread (for example, ref 12).…”
Section: Staphylococcus Aureus Myelitis S Karakonstantis Et Almentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] Table 2 summarizes findings from previous case reports. Of note is the fact that S.aureus myelitis has been described even without contiguous spread (for example, ref 12).…”
Section: Staphylococcus Aureus Myelitis S Karakonstantis Et Almentioning
confidence: 99%
“…Emboli formation can be iatrogenic: embolic material to the spinal cord vasculature is reported in a pediatric patient undergoing sclerotherapy of esophageal varices [56]. Thrombotic vasculitis and/or occlusive arachnoiditis was implicated in cord infarction of many children with central nervous system infections [53,[57][58][59][60][61][62][63][64][65][66][67][68][69]. Several thrombotic disorders have been reported in cases of spinal cord infarction [70][71][72][73][74][75].…”
Section: Causes Of Spinal Cord Infarction In Childrenmentioning
confidence: 99%
“…4 Hypotension Cardiac arrest [29] 6 Cardiac tamponade [30] 1 Arteriovenous malformation Vascular steal [32] 1 Mechanism unknown [31] 5 Thrombotic disorders Prothrombin variant [70,71] 2 Protein S deficiency [75] 1 Primary antiphospholipid syndrome [72] 1 Systemic lupus erythematosis [17,77] 3 Infectious disease Bacterial meningitis [53,[57][58][59][60][61][62][63][64][65][66][67] 15 Amebic menigoencephalitis [69] 1 Viral encephalitis [68] 1 Cerebellar herniation Metabolic encephalopathy [50] 3 Minor trauma [41][42][43][44][45][46][47][48] 18 Fibrocartilaginous embolism [1][2][3][85][86][87][88][89] 10 Cancer Anterior spinal artery thrombosis [76] 1 Atlanto-axial instability Achondroplasia [22] 1 I-cell disease [20] 1 Iatrogenic Sclerotherapy of esophageal varices [56] 1 Prolonge...…”
mentioning
confidence: 99%
“…2 It is very rare for bacterial meningitis to be complicated by spinal cord dysfunction. 4 Reported mechanisms for spinal cord dysfunctions include infarction due to vasculitis, direct infection of the cord-and immune-mediated inflammatory myelopathy. [5][6][7] Choudhary et al 7 recently reviewed the literature and could locate only eight reported cases of meningococcal meningitis causing myelopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The residual deficits of motor weakness, spasticity and sphincter disturbances are similar to other reported cases of thoracic myelopathy after meningococcal meningitis. 6 …”
Section: Discussionmentioning
confidence: 99%